2014
DOI: 10.1080/02678292.2014.913721
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mesogenic properties of 5-alkoxy-2-(4-alkoxyphenyl)pyrimidine liquid crystals: the effect of a phenoxy end-group in two sterically equivalent series

Abstract: Lemieux (2014) Tuning the mesogenic properties of 5-alkoxy-2-(4-alkoxyphenyl)pyrimidine liquid crystals: the effect of a phenoxy end-group in two sterically equivalent series, Liquid Crystals, 41:9, 1246-1260, Two sterically equivalent series of phenoxy-terminated 5-alkoxy-2-(4-alkoxyphenyl)pyrimidine liquid crystals were synthesised, and their mesogenic properties were characterised by polarised optical microscopy and differential scanning calorimetry (DSC). The phenoxy end-group causes a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Phenoxy end-groups have been reported to suppress SmC phases, 19 and the positions of fluorine substituents on phenoxy end-groups have been shown to influence the relative stabilities of the SmA and SmC phases. 20 In some cases, bulky non-polar end-groups have been proposed to preclude liquid-crystalline phases 16 and weaken interlayer interactions 21 due to their volume, but other studies have suggested that such groups may increase the temperature range over which the SmA phase is stable, 18 or enhance the stability of the SmC phase over the SmA phase.…”
Section: Introductionmentioning
confidence: 99%
“…Phenoxy end-groups have been reported to suppress SmC phases, 19 and the positions of fluorine substituents on phenoxy end-groups have been shown to influence the relative stabilities of the SmA and SmC phases. 20 In some cases, bulky non-polar end-groups have been proposed to preclude liquid-crystalline phases 16 and weaken interlayer interactions 21 due to their volume, but other studies have suggested that such groups may increase the temperature range over which the SmA phase is stable, 18 or enhance the stability of the SmC phase over the SmA phase.…”
Section: Introductionmentioning
confidence: 99%
“…28 In the monofluoro series QL20-m/n-xF, we chose to examine the same three representative isomers featured in Fig. 18 As shown in Fig. Modeling of intermolecular correlations in the SmA phase formed by the parent isomers QL11-m/n suggest that the phenylpyrimidine cores are approximately in register in the intercalated bilayer structure formed by QL11-10/6, and partially offset to bring the pyrimidine rings in register in the case of QL11-8/8, and the phenyl rings in register in the case of QL11-12/4.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…18 To assess the validity of these measurements, the samples were doped with the chiral additive MDW797 (2-5 mol%) and tilt angles were measured electrooptically by switching the SmC* phase between opposite tilt orientations as SSFLC films aligned in the same glass cells. 18 To assess the validity of these measurements, the samples were doped with the chiral additive MDW797 (2-5 mol%) and tilt angles were measured electrooptically by switching the SmC* phase between opposite tilt orientations as SSFLC films aligned in the same glass cells.…”
Section: Optical Tilt Angle Measurementsmentioning
confidence: 99%
See 2 more Smart Citations